Strategi Pengembangan Wisata Kuliner Desa Wisata Kampung Lama Kabupaten Deli Serdang Berbasis Potensi Lokal - Narwastu Murni (Politeknik Pariwisata Medan, 2023)
This study aims to explore strategies for developing culinary tourism in Kampung Lama Tourism Village, Deli Serdang Regency, by utilizing existing local potential. Deli Serdang Regency has a wealth of culture, history and culinary heritage that can be an attraction for tourists. Kampung Lama Tourism Village, as one of the tourist destinations in the area, has great potential in developing culinary tourism based on local potential. The research method used is qualitative research with a case study approach. Data collection was carried out through in-depth interviews with local culinary business owners, the local community, and related parties in the Kampung Lama Tourism Village. In addition, direct observation of culinary activities and analysis of related documents were also carried out. The results of the study show that the local potential in Kampung Lama Tourism Village is very diverse, including cultural wealth, culinary heritage, and natural beauty. Traditional food is one of the main attractions in culinary tourism in the old village. Some traditional recipes that have been passed down from generation to generation are distinctive and unique. However, more effective development and marketing efforts are still needed to increase the attractiveness and visibility of these traditional foods. Based on the research results, a local potential-based culinary tourism development strategy was developed in the Kampung Lama Tourism Village. This strategy includes leveraging local potential in traditional food, utilizing local raw materials, skills training for culinary entrepreneurs, effective promotion through social media and culinary exhibitions, as well as the active involvement of the local community in managing and promoting local culinary delights. This research is expected to contribute to the development of culinary tourism in Kampung Lama Tourism Village, Deli Serdang Regency. By exploiting existing local potential, it is hoped that culinary tourism can become one of the main attractions for visiting tourists, as well as providing economic benefits and preserving local culture